CHALLENGES OF USING ENGLISH AS A MEDIUM OF INSTRUCTION (EMI) IN THAILAND: Received: 09th November 2021; Revised: 05th June 2022, 17th June 2022; Accepted: 18th June 2022 - Tipprachaban, Benjawan (PUPIL: International Journal of Teaching, Education and Learning, 2022)
This article aims to review the situation of English education in Thailand at present. Thailand has put much effort into improving Thai people’s English proficiency all along. Even if various reforms in education, policies, and initiatives concerning English language teaching have been launched to develop the abilities of English-speaking Thais, slow progress has been made. Thai English proficiency remains among the lowest, despite government efforts from the past to the present. As globalization has accelerated due to transportation and technological advances, the use of English has occupied a major role in international communication. Using English as a medium of instruction has also been a goal of the Thai government. However, no matter how hard the previous and current governments have tried to improve the Thai people’s English competence, it seems the Thai people’s proficiency is always behind. This article discusses why Thai people remain incompetent in English and what the factors impeding Thailand’s ability to use English as a medium of instruction are. Also, ideas are given for how Thailand could get past the English language fallacy and become a country where English is used to teach.